Diagnostic Analysis of Family Understanding of School Curriculum Goals and Structure - Naylur Rosyid; Eha Suhayari (Elementaria: Journal of Educational Research, 2025)
The role of families in education is increasingly strengthened with the implementation of the Independent Curriculum, which positions students as the subjects of learning and emphasizes competency and character development. However, the success of curriculum implementation is determined not only by the readiness of schools and teachers, but also by families' understanding of the objectives and structure of the school curriculum. This study aims to diagnostically analyze the level of family understanding of the objectives and structure of the elementary school curriculum. The study used a descriptive approach with a diagnostic study design. The subjects were families of elementary school students at SDN Sukasari 1, Sukasari Village, Pulosari District, Pandeglang Regency. Data were collected through diagnostic questionnaires and structured interviews, then analyzed descriptively quantitatively and qualitatively. The results showed that families' understanding of the curriculum objectives was in the moderate category, while their understanding of the curriculum structure was in the low category. These findings indicate a gap in curriculum literacy among families that has the potential to impact the effectiveness of student learning support at home. This study contributes by providing an initial mapping of family curriculum literacy that can serve as a basis for formulating school-family communication and partnership programs to support the implementation of the Independent Curriculum.